Use of Technology in Human Resource Management in the Industrial Era 4.0 - Ramadhan, Muhammad Umar; Rachman, Deddy; Ramadhan, Muhammad Novryan; Khuzaini, Khuzaini; Auliah, Nurul; Shaddiq, Syahrial (PT. Hanken SUkses Jaya, 2024)
The Industrial Era 4.0 has brought disruptive technological innovation, crossing physical and digital boundaries completely, and changing the way people carry out daily life activities and at work. Technological breakthroughs create opportunities for economic, social and individual growth, but artificial intelligence (AI) will take over human jobs. Human resource development readiness is important to overcome every obstacle in the 4.0 era. The aim of this research is to describe human resource development strategies that face challenges in the industrial era 4.0. The type of research method is descriptive analysis. The results show that a successful HRD strategy involves more than education, coaching, training, institutions, opportunities and rewards. Human resource management must increase creativity, change a fixed mindset into a growth mindset, adapt to science and technology and make changes, create superior human resources and adapt to the influence of the new era entering the social era. 5.0.